Biochar de casca de pequi como condicionador de solo no desempenho agronômico de feijoeiro - Maria Shirley Amorim Silva (2017)
Aiming to evaluate the effect of pequi bark biochar (BCP) as soil conditioner and its influence on the agronomic characteristics of common bean (Phaseolus vulgaris L.), an experiment was carried out in a plant nursery. It was used an experimental design in randomized block, factorial scheme 4x3 + 2, being the factors consisted of four doses of biochar: 2.5; 5.0; 7.5 and 10 (% v / v) and three granulometries: <0.5 mm, granulometry 1; 0.5 - 1.0 mm granulometry 2; 1.0 - 2.0 mm granulometry 3, two control treatments, being one with natural soil, that is, without any addition of biochar and the other with limestone and without biochar. It was evaluated the physical characterization of the pequi fruit, the chemical characteristics of the soil before and after the experiment implantation, the agronomic performance of the bean crop by mean of aerial dry mass (MSPA) and dry mass of the roots (MSR) and the nutrient content in MSPA. The physical characterization of the fruit of pequizeiro showed higher yield of the external mesocarp with 73.71% of mass in relation to the pyrenean with 26.29%. The pyrolysis of the bark provided a reduction of 94.36% of the original biomass. The chemical attributes of the soil were influenced by the BCP, which promoted positive changes in soil acidity components, raising the pH and reducing the exchangeable Al and potential acidity, presenting potential to function as a soil conditioner, mainly to the granulometry <0.5mm. As for nutrient supply, BCP did not increase their availability in the soil, due to the low concentration, except for the organic K and C with the greatest increment for the granulometry <0.5 mm. For the agronomic characteristics, the larger granulometries favored a better production of the root dry mass and the aerial part, with a similar or superior response to the corrected soil with limestone. Only the K was positively influenced by the content, due to the increase in the concentration of this nutrient in the soil, its increase occurred in the content of the MSPA, mainly for the granulometry <0.5 mm. The other nutrients had little or no influence. Thus, BCP positively influences some attributes of the soil, being that, when it was not higher, it was equal to the control treatment with limestone, demonstrating the ability to function more as a soil corrective than as a nutrient supplier. It is still verified the potentiality of itself in can serve as a mixture with other residues or nutrient-rich materials to balance of their availability to the soil.